The Influence Of Intellectual Capital And Leverage On Financial Performance In Banking Companies Listed On The Indonesian Stock Exchange - Asmaul Husna; Meti Zulyana; Septa Aryani, Dwi; Mikial; Ima Andriyani (International Journal of Management and Business Economics, 2024)
This study aims to analyze the influence of intellectual capital, institutional ownership and leverage on financial performance in banking companies listed on the Indonesia Stock Exchange. The Financial Performance of Banking Companies is measured using Return on Equity (ROE) as the main indicator. The data used in this study are secondary data obtained from the annual reports of banking companies listed on the IDX during the 2019-2022 period through the website www.idx.co.id. The analysis method used in this study is multiple linear regression. The results of the study simultaneously show a significant, which means that intellectual capital, institutional ownership and leverage simultaneously affect the financial performance of banking companies listed on the Indonesian Stock Exchange. The results of the study partially show a significant, which means that intellectual capital and institutional ownership have a positive and significant effect on the financial performance of banking companies, while leverage has a negative and significant effect on the financial performance of banking companies listed on the Indonesian Stock Exchange. It is expected that further research can use other independent variables, such as liquidity and company size with different observation periods.